PENERAPAN MEDIASI PENAL DALAM PENYELESAIAN TINDAK PIDANA PERKELAHIAN MENURUT HUKUM ADAT KAMPAR - Ismi Anandita; Erdianto '; Rahmat Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The republic of Indonesia is a state law, in view of life based on Pancasila as a philosophy of the country. Indonesia is a state of the republic with the constitution of 1945 as a legal basis. Of the republic of Indonesia consists of various tribes, so make the nation of Indonesia has a variety of language, culture, rase, and customs. The cultural values is the most high and most abstract of customs. That’s because the values of that culture is the concepts of what life in the mind, most of the citizens of something the public about what they consider valuable, precious and most impirtant in life, so it can serve as a guideline that gives direction and orientation to the life of the people. In addition to the national law, in the middle of the public is growing and developing a system of law, which comes from an existing habit in the community are down from generation to generation. The habit of this is what evolved into a provision called the customary law.In Indonesian positive law, criminal cases here to be resolvedin court. However, in special cases these can be solved. Outside court for example is penal mediation, as alternative solution in costumary law in Kanagarian Kuok. Completion of the criminal case through a process outside the court today increasingly frequent and can be accepted by the public because it is felt more able to reach a sense of justice although legal experts view that mediation can only be implemented in a civil case is not to resolve the criminal case because in principle criminal case can not be resolved through process aoutside the court.In the of completion fighting criminal case is still adhering mediation that using kinship by deliberation for reaching dicision based on customary law that condicted by intermediation pemangku adat. With the criminal offense of mediation in the settlement of a fight in Kenagarian Kuok, then eliminated criminal sanction against him because people in Kenagarian Kuok more respect customary law and if a criminal case has been resolved through customary law in the national criminal law is not used anymore.Key Words: Penal Mediation - Fight – Customary Law